Exploring unusual metastasis in carcinoma breast: Divulging vulval metastasis (Indian Journal of Case Reports, 2019)
Regional lymph nodes, bones, brain, lung, and liver are the most common sites of the breast carcinoma metastases. Nodular or ulcerated lesions over the vulva are ignored for a long time as benign lesions by the patient and there is a lot of hesitance to undergo the examination. Here, we report the case of a 41-year-old female with an isolated, asymptomatic vulval metastasis of Invasive ductal carcinoma of the breast. The purpose of reporting this case is to make the clinicians aware of this rare site of metastasis of breast cancer and the importance of pelvic examination in follow-up patients.